Refinement and Validation of a New Patient‐Reported Experience Measure for Hearing Loss (My Hearing PREM) - Sian K. Smith; Helen Pryce; Georgina Burns O'Connell; Rebecca C. Knibb; Rosemary Greenwood (Health Expectations)
ABSTRACT Context Patient‐reported experience measures (PREMs) generate insights into daily challenges experienced when living with a chronic condition and experiences of care. There are no validated PREMs to measure the experience of hearing loss. Objective The aim of this study was to evaluate the psychometric properties of a newly developed tool, ‘My Hearing PREM’, designed to assess the experience of living with hearing loss and receiving audiology care. Setting and Participants Adults with hearing loss (n = 401) were recruited from audiology clinics in Scotland and England, and non‐clinical routes such as lip‐reading classes, clinical research networks, national charity links and social media. Design Participants completed a 27‐item PREM alongside validated scales to measure communication difficulties, loneliness, quality of life, decisional conflict and health literacy. Modern (Rasch) and traditional psychometric analysis techniques (internal consistency and construct validity) were used to assess the psychometric properties of the My Hearing PREM. Results Factor analysis of the initial 27 items produced 3 subscales: Emotional Burden, Support and Communication, after 4 items were removed due to poor fit. Rasch analysis was carried out on each of these subscales and a further 7 items with poor fit to the Rasch model were removed. This resulted in a long‐form 16‐item (My Hearing PREM‐16) demonstrating good internal reliability (Cronbach's α = 0.91). Each subscale showed good internal reliability (0.91, 0.85 and 0.71). A short‐form (My Hearing PREM‐9) version was developed for use in clinical practice (α = 0.79). Both forms of the PREM demonstrated medium to strong significant correlations with the validated measures. Conclusion Both the My Hearing PREM‐16 and My Hearing PREM‐9 are reliable measures with good construct validity. They provide a way for healthcare professionals to understand how hearing loss is affecting an individual's emotional well‐being, social interactions and communication. Ongoing research is exploring the feasibility of My Hearing PREM in routine audiology practice. Patient or Public Contribution We developed the project in collaboration with members of the public who have lived experience of hearing loss, recruited through Aston University and volunteer networks connected to audiology services. Additionally, we engaged with individuals more likely to be impacted by hearing loss, including adults with learning disabilities, older adults in residential care, and members of South Asian communities (Bangladeshi, Indian and Pakistani). These stakeholders provided valuable feedback on the study's aims, the content and format of the My Hearing PREM items, the survey design and recruitment strategies.